Promoting Students' English-Speaking Skills Using English Speaking Practice Application - Wahono, Suparwoto Sapto; Machfudi, Moch. Imam (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2023)
Speaking is a practical skill and serves as a crucial indicator of one's proficiency in English. Generally, an individual is considered to have a strong command of the English language if they can effectively communicate verbally. Mastery of speaking skills is particularly challenging, as it necessitates consistent practice. To address the challenges faced by students in developing their English speaking abilities, researchers implemented the English-Speaking Practice (ESP) application as a resource for facilitating English conversation. This study aimed to enhance students' speaking skills across various dimensions, including pronunciation, grammar, vocabulary, fluency, and comprehension. Employing a participatory action research methodology, data was gathered through observations, interviews, and assessments. The findings indicated that the ESP application, featuring a